TPC POPULATION AND PHYSICAL QUALITY OF BALINESE BEEF WITH MARINATION USING EXTTRACT WULUH STARFRUIT (AVERRHOA BILIMBI L) - N. K. E. T., Pratiwi; Sriyani, N.L.P; Wibawa, A.A.P.P (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
This study aims to find out the effect of marination with different concentrations using a wuluh starfruit (averrhoa bilimbi) solution on the total plate count and physical quality of Balinese beef. This study was conducted in September 2020 - October 2020 at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University. The study was conducted using a completely randomized design (CRD) with 4 treatments and 4 repetitions. The four treatments were: the beef was marinated using only distilled water (P0), the beef was marinated using wuluh starfruit solution with a concentration of 20% (P1), the beef was marinated using wuluh starfruit solution with a concentration of 40% (P2), and the beef was marinated using wuluh starfruit solution with a concentration of 60% (P3). The variables observed were total plate count and physical quality of beef including, pH, color, water holding capacity, cooking loss, and raw loss. The results showed that Balinese beef marinated using the wuluh starfruit solution with a concentration of 0, 20%, 40% and 60% obtained the total plate count was 6.5 x 106 cfu / g - 3.3 x 105 cfu / g; pH value was 5.06 - 3.45; colors was 2.00-1.00; DIA was 27.44% - 22.88%; cooking loss was 31.45% - 37.29%; raw loss was 12.80% - 16.82%. The best results based on the total plate count value was the P3 treatment with a solution concentration of 60%, whereas when viewed from the physical quality of the beef, the P0 treatment marinated without wuluh starfruit solution obtained the best results. Keywords : physical quality, total plate count, wuluh starfruit, beef